Pengaruh Lingkungan Keluarga Terhadap Pembentukan Nilai Agama dan Moral Anak Usia Dini - Widiyanti, Suci; Freliana Zeta, Retno; Nurul Azkiya, Rizka; Nur Halimah, Siti; Amelia, Ayunadya; Rukiyah; Ilhami, Akmillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of the family environment on the development of religious and moral values in early childhood. The family is the primary educational environment for children and plays a crucial role in shaping both positive and negative behavioral habits through habituation, role modeling, and parenting practices. This study employs a literature review approach by examining various scholarly sources related to religious education and children’s moral development. The findings reveal that families that are harmonious and religious, and that provide good examples through worship practices, positive communication, and the cultivation of moral values, are able to shape children’s character to be virtuous and possess integrity from an early age.